PENGEMBANGAN MEDIA PEMBELAJARAN MENGGUNAKAN ARTICULATE STORYLINE 3 BERBASIS ANDROID PADA ELEMEN NEGARA KESATUAN REPUBLIK INDONESIA (STUDI PADA FASE E SMA NEGERI 1 SUKOHARJO) - Ginkha Aryana, Arsyad; Al Rasyid, Machmud; Wijianto, Wijianto (Jurnal Global Citizen : Jurnal Ilmiah Kajian Pendidikan Kewarganegaraan, 2025)
This study aims to (1) Develop learning media using Articulate Storyline 3 based on android on the elements of the Unitary State of the Republic of Indonesia in phase E of SMA Negeri 1 Sukoharjo; (2) Measure the feasibility of the product of the development of learning media using Articulate Storyline 3 based on android on the elements of the Unitary State of the Republic of Indonesia in phase E of SMA Negeri 1 Sukoharjo. The results of this study are (1) the development of learning media based on android on the elements of the Unitary State of the Republic of Indonesia in the form of an application containing learning materials, learning videos and evaluations (multiple choice tests). (2) The development product was validated by experts with the results of the feasibility test based on the validation of material experts of 76.25%, and the validation of media experts of 82%. Furthermore, a limited trial was conducted with a score of 90.1% and the results of the extensive trial obtained a score of 89.2%. The results of the effectiveness test using N-gain on class X E8 students obtained a score of 0.76 and on class X.E11 students obtained a score of 0.75. Keywords: Learning Media, DBR, Articulate Storyline 3, Pancasila Education